Social patterns and dynamics of creativity in Wikipedia. (2016) - Launonen, Pentti; Tiilikainen, Sanna; Kern, K.C.
Our paper explores contribution and self-organising patterns of creative collaboration among Wikipedia editors as manifestations of social dynamics between the editors. We collect contribution data from a random sample of Wikipedia articles and use a novel approach of analysing the correlations between editors' contribution patterns over the life-time of the articles. We find support for the existence of four socially conditioned personas among the editors and statistical difference in distribution of personas in articles of different qualities. Our findings add domain-specific details, features and attributes to the existing knowledge on editor roles and personas. Contributions to theories of the implicit self-organisation of collaborative innovation networks and creativity as well as implications for practise are discussed.